Quantitative Evaluation of Proteinuria with Urinalysis Test and Comparing ItsCorrelation with Random Spot Urine PCR and 24-Hour Urine Protein in SLEPatients - Chun Ruh Ng (Indonesian Journal of Rheumatology, 2022)
Introduction: Lupus nephritis is an important concern among systemiclupus erythematosus (SLE) patients in Asia, and its mortality rate wasreported to be 6 times higher compared to the general population. 24-hoururine protein collection has long been used as the gold standard test toassess proteinuria. This study aimed to assess the correlation of urinalysistest with random spot urine protein-creatinine ratio (PCR) compared with24- hour urine protein. Methods: This was a retrospective study. Theelectronic medical records of all SLE patients seen in the rheumatology clinic of Hospital Sultan Ismail from 1st January 2017 to 1st January 2021 were reviewed. Patients who had urinalysis, urine protein-creatinine ratio, and24-hour urine protein tests were identified. Data on demography, urinalysis, random spot urine protein-creatinine ratio, and 24-hour urine protein were obtained and analysed. Results: The correlation between urinalysis and 24hour urine protein was strong (r=0.702), whereas the correlation betweenurinalysis and urine PCR was stronger (r=0.797). Our study also showed thecorrelation between random urine protein-creatinine ratio and 24-hour urineprotein is strong (r=0.782). Conclusion: Urinalysis correlates well with bothrandom spot urine protein-creatinine ratio and 24-hour urine protein, andthe correlation is stronger with urine protein-creatinine ratio.